From Ritual Theory To a Spiritual Biology: Prayer and the Activation of Chakras-Hormones in Human Metabolism - Aris Widodo; Dwi Purbowati (Ulumuna, 2022)
Prayer as one of the essentials of human beings as "homo Deus", has become the object of studies from diverse perspectives: theosophical, sociological, psychological, phenomenological, and even political. This study will, however, shed light on this issue from another angle, namely a bio-spiritual standpoint, since the human being is made up of psycho-somatic features, or body, mind, and soul, with particular reference precisely to the human metabolism: endocrine system. This article will argue that human hormones, which have a pivotal role in human metabolism, are related to seven glands. These glands are actively managed to be stipulated by the activation of seven subtle energy centers, chakras, which can be done, among other things, by prayer (ṣalāh). To say the other way round, prayer (ṣalāh) will activate the seven chakras that will, in turn, stimulate the seven glands of the human endocrine system and will eventually boost the hormones that are significant for human life. In this way, this study will provide more illustration where "Scientia Sacra" (sacred science), concerning prayer (ṣalāh), meets "profane" science in a sort of "spiritual biology."